PEG‐fibrinogen hydrogels for three‐dimensional breast cancer cell culture. Issue 1 (14th October 2016) - Pradhan, Shantanu; Hassani, Iman; Seeto, Wen J.; Lipke, Elizabeth A.
Abstract: Tissue‐engineered three‐dimensional (3D) cancer models employing biomimetic hydrogels as cellular scaffolds provide contextual in vitro recapitulation of the native tumor microenvironment, thereby improving their relevance for use in cancer research. This study reports the use of poly(ethylene glycol)‐fibrinogen (PF) as a suitable biosynthetic hydrogel for the 3D culture of three breast cancer cell lines: MCF7, SK‐BR‐3, and MDA‐MB‐231. Modification of the matrix characteristics of PF hydrogels was achieved by addition of excess poly(ethylene glycol) diacrylate, which resulted in differences in Young's moduli, degradation behavior, release kinetics, and ultrastructural variations in scaffold microarchitecture. Cancer cells were maintained in 3D culture with high viability within these hydrogels and resulted in cell‐type dependent morphological changes over time. Cell proliferation and 3D morphology within the hydrogels were visualized through immunofluorescence staining. Finally, spatial heterogeneity of colony area within the hydrogels was quantified, with peripheral cells forming colonies of higher area compared to those in the interior regions. Overall, PF‐based hydrogels facilitate 3D culture of breast cancer cells and investigation of cellular behavior in response to varying matrix characteristics. PF‐based cancer models could be potentially used in future investigations of cancer biology and in anti‐cancer drug‐testing applications. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 236–252, 2017.